2018
DOI: 10.18006/2018.6(1).230.235
|View full text |Cite
|
Sign up to set email alerts
|

EFFECT OF SAUDI ARABIAN Capparis Cartilaginea FRUIT EXTRACTS ON SERUM PARATHYROID HORMONE AND 1α,25-DIHYDROXYVITAMIN D3 LEVELS IN RATS

Abstract: Capparis cartilaginea is a shrub plant which used in traditional medicine to cure various diseases. Phytochemical analysis of Capparis cartilaginea plants extracts revealed the presence of isothiocyanates and flavonoids. A dose dependent study was designed to assess effects of Capparis cartilaginea fruit extract on serum parathyroid hormones (PTH) and 1α,25-Dihydroxyvitamin D3 (1α,25(OH)2D3) levels in adult male and female Wistar rats, which could describe a regulation effect on bone metabolism. Healthy adult … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Mice-fed As + QC also displayed significantly higher Trpv6 expression in the duodenum (2.00 ± 0.70 vs 0.88 ± 0.28, p < 0.05, Figure G), while ileal Trpv6 expression was also elevated although not significantly (Figure H). Studies reported increased serum PTH levels with flavonoids in rat and upregulated serum 1,25­(OH) 2 D 3 in broilers . Among the test five polyphenols, QC and EGCG are flavonoids that possess estrogen-like effects.…”
Section: Resultsmentioning
confidence: 99%
“…Mice-fed As + QC also displayed significantly higher Trpv6 expression in the duodenum (2.00 ± 0.70 vs 0.88 ± 0.28, p < 0.05, Figure G), while ileal Trpv6 expression was also elevated although not significantly (Figure H). Studies reported increased serum PTH levels with flavonoids in rat and upregulated serum 1,25­(OH) 2 D 3 in broilers . Among the test five polyphenols, QC and EGCG are flavonoids that possess estrogen-like effects.…”
Section: Resultsmentioning
confidence: 99%
“…Then, 50 g of the dried fruit powder was used to create 11.5 g of dried extract. The final extract was stored at -80°C for later use [6].…”
Section: Plant Materials and Preparation Of Ethanolic Extractmentioning
confidence: 99%
“…Our research group has been studying the Capparis cartilaginea (C. cartilaginea) fruit extract and has published on the many beneficial aspects of this plant. It has been found to possibly reduce and treat osteoporosis and could alter the levels of the parathyroid hormone (PTH) and 1α,25-Dihydroxyvitamin D3 (25(OH)2D3) hormone [5,6]. Moreover, it induced morphological alterations in 22RV1 human prostate cancer cells and had a notable impact on cell death and mortality.…”
Section: Introductionmentioning
confidence: 99%